Laboratory and Clinical Predictors for Gestational Diabetes Mellitus among Kosovo Pregnant Women - Emini-Sadiku, Merita; Sadiku, Izet; Lulaj, Shefqet; Kocinaj, Venera; Sopjani, Mentor (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Gestational diabetes mellitus (GDM) is a condition increasing yearly worldwide. AIM: We investigated the prevalence and the arrangement of common risk predictors for developing GDM among Kosova pregnant women after 24 gestational weeks. MATERIALS AND METHODS: A total of 202 hospitalized pregnant women participated in this prospective study. All participants underwent a detailed clinical examination for risk factors for GDM, followed by appropriate biochemical blood analysis and anthropometric measurements. The glucose tolerance test results were interpreted according to the criteria established by the World Health Organization (WHO) and American Diabetes Association. Participants in the first part of the study were divided into the four risk groups and in the second part GDM group (case group) or a normal glucose tolerance group (control group) to determine the risk factors for GDM and associated clinical and biochemical predictors. RESULTS: The prevalence of gestational diabetes was 5.9%.The average age was 30.0 ± 5.5. Main characteristics of high-risk group of women for GDM were: ages above 30-year-old (p = 0.001), positive glucose intolerance (p = 0.0001), personal history for GDM (p = 0.0001), familiar history for DM (p = 0.0001), obesity (p = 0.0001), previous childbirth with weight higher than 4000 g (p = 0.0001), vulvovaginal infection (p = 0.0001), and polyhydramnios (p = 0.0001). Almost the same characteristics were found also for the GDM group: Like personal history for GDM (p = 0.0018), and family history for DM (p = 0.0018). Moreover, the group with GDM was characterized with significantly higher laboratory parameters such as fasting glycemia (p = 0.0000), triglycerides, and cholesterol concentrations (p = 0.0001). Anthropometric measurements such as weight (p = 0.002), body mass index (p = 0.0015), and systolic (p = 0.0163) and diastolic (p = 0.042) blood pressure were also significantly higher than the control group. CONCLUSIONS: Older age, family history of diabetes and personal history for GDM, polyhydramnios, stillbirth >4000 g, were significant risk factors for GDM. Screening for risk factors can easily bring at GDM early diagnosis and prevention. Public awareness-raising on the risk factors for GDM and the need for early screening should be strongly pursued, particularly for the women at risk for GDM, especially in developing countries. At every level of health service, GDM screening to pregnant women should be incorporated as a routine antenatal visit.